2021
DOI: 10.1177/15330338211055340
|View full text |Cite
|
Sign up to set email alerts
|

The Clinicopathological Features and Overall Survival of Patients With Gastric Neuroendocrine Carcinoma

Abstract: Objectives: Gastric neuroendocrine carcinoma (GNEC) is a class of rare histological subtypes in gastric cancer (GC). This retrospective case-control study aimed to explore the clinicopathological features and overall survival (OS) of patients with GNEC. Methods: A large population of GNEC and intestinal-type GC (IGC) patients were extracted from the Surveillance, Epidemiology, and End Results (SEER) database. The 1:1 propensity score matching (PSM) analysis was initiated to adjust the confounders between GNEC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
2
3
0
Order By: Relevance
“…Besides, recent studies indicated that poorly differential NENs had a good response to the chemotherapy, which might explain the better OS of patients with NENs [ 19 , 20 ]. Moreover, recent studies have reported that gastric NEC has unique clinicopathological features quite different from intestinal-type gastric cancer (IGC) and may have a superior survival to IGC in early-stage patients, indicating that NENs have better survival than other pathological types of cancers, like adenocarcinoma [ 21 , 22 ], which is consistent with our research.…”
Section: Discussionsupporting
confidence: 92%
“…Besides, recent studies indicated that poorly differential NENs had a good response to the chemotherapy, which might explain the better OS of patients with NENs [ 19 , 20 ]. Moreover, recent studies have reported that gastric NEC has unique clinicopathological features quite different from intestinal-type gastric cancer (IGC) and may have a superior survival to IGC in early-stage patients, indicating that NENs have better survival than other pathological types of cancers, like adenocarcinoma [ 21 , 22 ], which is consistent with our research.…”
Section: Discussionsupporting
confidence: 92%
“…Then the subgroup analyses and multivariate competing risks regression analysis confirmed no significant relationship between chemotherapy and CSD. Patients in the chemotherapy cohort presented higher proportion of male, grade III/IV, primary site of cardia, and tumor size over 5 cm, which had been confirmed as high-risk factors in previous studies [ 18 ]. Therefore, a lower percentage of high-risk variables in the no-chemotherapy cohorts and other probable comorbidities not recorded in the SEER database might help partially explain the difference in OCD between the two groups.…”
Section: Discussionsupporting
confidence: 66%
“…Xu et al conducted a comparative study between intestinal-type GC (IGC) and GNEC patients, demonstrating that GNEC patients presented a longer survival to ICG in the early-stage tumor. And age, gender, tumor size, AJCC stage, T stage, N stage, and surgery were considered the risk factors with the OS of GNEC patients [ 18 ]. As in our study, the multivariate competing risk analysis found older age, male gender, greater tumor diameter, and higher TNM stage as independent risk factors for CSD.…”
Section: Discussionmentioning
confidence: 99%
“…Dasari et al [ 21 ] found that in distant gastrointestinal neuroendocrine neoplasms, Asians or Pacific Islanders were identified as an independent risk factor associated with poor prognosis compared with Whites. However, a recent study [ 23 ] did not recognize race as an independent risk factor related to prognosis in patients with GNEC. In this study, with 653 GNEC patients, there were just three categories of the race including Whites, Blacks, and others, which did not split up Asians separately as a race.…”
Section: Discussionmentioning
confidence: 99%